Tutor preference and perception for the type of pet animal transportation on commercial flights (Research, Society and Development, 2021)
Pets have been increasingly integrated into family activities. In view of this tendency, the objective of this study was to assess the preference of tutors for the air transport conditions offered in a commercial situation to their animals (cabin or cargo hold). Tutors' concerns about animal welfare, their insecurity in relation to the air transport services and the importance given to airport infrastructure were also assessed. Data were collected for eight months, by applying two questionnaires. For the first questionnaire, 80 tutors were selected, carrying at least one dog or cat, in both national and international flights. The second questionnaire was applied to 157 individuals who owned at least one pet and intended to board it along on commercial flights, whereas hedonic scales composed response options for each factor. 58% of tutors chose to board their pets in the passenger cabin and 42% in the aircraft cargo hold. Most of the factors related to animal welfare during the flight were considered "extremely worrying". Tutors were "extremely insecure" when hiring air services and considered the factors related to the infrastructure of the airports "very important" for their animals. The “extreme concern” with the mistreatment of animals (74.4%), the “extreme insecurity” with the possibility of extraviation of the animals (76.0%) and the “great importance” given to guarantees of animal welfare and safety at the airports (91.1%) were very relevant in this research. Therefore, it is concluded that tutors prefer to transport their pets in the cabin, as a way to guarantee animal welfare during the flight.